Flexible active compensation based on load conformity factors applied to non-sinusoidal and asymmetrical voltage conditions - Brandão, Danilo I.; Parades, Helmo K.M.; Costabeber, Alessando; Marafão, Fernando P. (IET, 2016)
This study proposes a flexible active power filter (APF) controller operating selectively to satisfy a set of desired load performance indices defined at the source side. The definition of such indices, and of the corresponding current references, is based on the orthogonal instantaneous current decomposition and conformity factors provided by the conservative power theory. This flexible approach can be applied to single- or three-phase APFs or other grid-tied converters, as those interfacing distributed generators in smart grids. The current controller is based on a modified hybrid P-type iterative learning controller which has shown good steady-state and dynamic performances. To validate the proposed approach, a three-phase four-wire APF connected to a non-linear and unbalanced load has been considered. Experimental results have been generated under ideal and non-ideal voltage sources, showing the effectiveness of the proposed flexible compensation scheme, even for weak grid scenarios.